Crime corporativo, meio ambiente e esfera pública: uma análise da realidade do município de mossoró, a partir da perspectiva do ministério público. - Melo, Esaú Castro de Albuquerque (Universidade Federal Rural do Semi-Árido, 2019)
Modern corporations have become one of the traces of modern society. Their prominence has advanced as much as the amount of problems related with environmental crime and resources spent by the government to contain them. This premise guides this work that questions to what extent environmental crimes can be committed by companies, thus assuming the typology of corporate crime. This work aims to understand how corporate environmental crimes occur in the city of Mossoró/RN, its frequency, and its relationship with the public sphere. Specifically, this understanding is based on a critical analysis at the Ministério Público of Mossoró, it's organization, how the management is done, and how its agents understand and deal with corporate environmental crime in the city. Methodologically we discuss the concepts of public sphere, typologies of corporate crimes, with emphasis on organizational studies. Other methodological resources in this research are the bibliographical and documentary research; the field research and semistructured interviews with representatives of the Ministério Público of Mossoró. This allowed us to verify at the local level typologies of environmental crimes that transcend corporate actions, to find a list of transgressions committed by individual agents; small companies and individual entrepreneurs. On the other hand, it also allowed us to understand and identify the "binary" characteristics involved in the management of the public sphere and its mechanisms of social control in the face of corporate environmental crimes. It can be concluded that corporations, as groups that hold the process of capital formation, place the maximization of their profits before the collective well-being, perpetrating social and environmental inequality, being imperative the protection of the environment and a better management of the public sphere
Keywords: Crime Corporativo; Meio Ambiente; Esfera Pública; Ministério Público; Mossoró/RN; Corporate Crime; Environment; Public Sphere; Prosecutions; Mossoró/RN; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA